P04.07 "Summer loving": an analysis of seasonal differences in sexual behaviour and sexually transmissible infections. (13th September 2015) - Cornelisse, VJ; Fairley, CK; Chow, EPF
Abstract : Introduction: Public health campaigns must be timed to target their audience at times of highest risk. To date no study has correlated seasonal differences in sexual behaviour with those in sexually transmissible infection (STI) positivity; and no seasonal study has been conducted in the southern hemisphere. Our study aimed to describe seasonal differences in sexual behaviour and correlate this with STI positivity. Methods: This was a cross-sectional study of individuals attending the Melbourne Sexual Health Centre (MSHC) over a 9 year period from 2006–2014 inclusive. We conducted separate analyses for women, men who have sex with men (MSM) and men who have sex with women (MSW). Seasonal patterns of sexual behaviour (partner numbers, condom use and injecting drug use), and STI positivity were examined in all groups. STI with a high symptomatic rate and short incubation period were selected for the analysis: gonorrhoea, primary herpes simplex virus (HSV) infections, non-gonococcal urethritis (NGU) (men only), and pelvic inflammatory disease (PID) (women only). Results: All groups reported a significantly higher number of partners in summer compared to winter (women P < 0.001; MSW P < 0.001; MSM P = 0.004). MSW reported less consistent condom use in summer (P = 0.016); a similar but non-significant trend was observed in MSM and women. The urethral gonorrhoea positivity among MSM was significantly higher in summer compared to winter (P = 0.017). Similarly, the NGU positivity among MSW was the highest in summer (P = 0.009). In women PID diagnoses climbed over summer to peak in autumn, which then dropped to a low in winter (P = 0.025). The other STIs did not show statistically significant seasonal differences. Conclusion: Our study describes a peak in sexual partner number and STI positivity in summer. This seasonal difference must inform the timing of public health campaigns, as these are likely to be maximally effective in spring and summer. Disclosure of interest statement: None.